Physical Planning Implications of Property Development in Akure Ondo State of Nigeria - Babade, Joseph Babatope (Obafemi Awolowo University, 2014)
Most urban problems have been attributed to the practice of property development in defiance of necessary planning considerations. The case of Akure is examined in this work. In this respect, questionnaires were served on 670 respondents in Akure. The questions require information on physical characteristics of various property types in Akure, and also, on the socio-economic characteristics of the occupiers. Various agencies responsible for urban affairs were contacted on the existing situation. In addition, the physical environment of Akure was critically studied to determine implications of various property types.